2011
DOI: 10.1152/ajpgi.00342.2010
|View full text |Cite
|
Sign up to set email alerts
|

The extracellular calcium-sensing receptor is required for cholecystokinin secretion in response to l-phenylalanine in acutely isolated intestinal I cells

Abstract: SA. The extracellular calcium-sensing receptor is required for cholecystokinin secretion in response to L-phenylalanine in acutely isolated intestinal I cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
119
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(131 citation statements)
references
References 48 publications
(44 reference statements)
10
119
1
Order By: Relevance
“…Recently, several groups have reported that the CaSR in cells within the lumen of the gastrointestinal tract is activated by L-Phe and other amino acids, which have long been recognized as activators of key digestive processes. Hence, the CaSR enables the tract to monitor events relevant to both mineral ion and protein/amino acid metabolism in addition to the sensing capability of CaSR in blood and other extracellular fluids (19,22,23). Glutathione and its ␥-glutamylpeptides also allosterically modulate the CaSR at a site similar to the L-amino acidbinding pocket but with over 1,000-fold higher potencies (20,24).…”
mentioning
confidence: 99%
“…Recently, several groups have reported that the CaSR in cells within the lumen of the gastrointestinal tract is activated by L-Phe and other amino acids, which have long been recognized as activators of key digestive processes. Hence, the CaSR enables the tract to monitor events relevant to both mineral ion and protein/amino acid metabolism in addition to the sensing capability of CaSR in blood and other extracellular fluids (19,22,23). Glutathione and its ␥-glutamylpeptides also allosterically modulate the CaSR at a site similar to the L-amino acidbinding pocket but with over 1,000-fold higher potencies (20,24).…”
mentioning
confidence: 99%
“…Several physiological secretagogues (such as monitor peptide and amino acids) as well as exposure to depolarizing concentrations of KCl increase [Ca 2+ ] i , which is linked to hormone release (7,8,23,24). In this study, involvement of calcium signaling in ILDR1-stimulated CCK secretion was demonstrated by comparing [Ca 2+ ] i in wild-type and Ildr1 -/-CCK-EGFP cells.…”
Section: Figurementioning
confidence: 86%
“…Like most gastrointestinal hormones, CCK is released into the blood following ingestion of a meal, and despite the apical surface being exposed to the lumen of the intestine, the mechanisms by which foods stimulate hormone secretion are largely unknown. It has recently been demonstrated that CCK cells contain calcium-sensing receptors that mediate amino acid-stimulated CCK release (7,8), supporting the concept that cell surface receptors regulate food-stimulated gastrointestinal hormone release. Of the food components that stimulate CCK secretion, fats are the most important.…”
Section: Introductionmentioning
confidence: 83%
“…We suggest that the CaRs play a role in dietary Pi recognition. Indeed, previous studies demonstrated that activation of CaRs in enteroendocrine G-cells and I-cells stimulates the secretion of gastrin and cholecystokinin, respectively (31,32). In addition, CaR detects Lamino acids within the concentration ranges of the diets (33,34).…”
Section: Discussionmentioning
confidence: 99%